The Evaluation of Human Tenon's Fibroblasts and Endothelial Cell Responses to Antifibrotics Alone and in Combination with α-Tocopherol. (January 2015) - Engin, Kaya N.; Erdem-Kuruca, Serap; Akgün-Dar, Kadriye; Çetin, Beyza; Karadenizli, Sabriye; Gürel, Ebru; Yemisci, Bülent; Bilgiç, Sema; Arslan, Mehmet
Abstract Purpose: We aimed to evaluate the influence of current antifibrotic agents as well as the possible results obtained by combining these agents. This study included α-tocopherol, a strong antifibrotic and an efficient neuromediator of pathways used by other agents. Materials and Methods: Mitochondrial Bcl-2, Bax, cytochrome c and cytoplasmic caspase-3 expression, as well as toxic effect patterns, mitosis and cellular reactions due to α-tocopherol alone or combined with paclitaxel, mitomycin C and 5-flurouracil (5-FU), was studied in series obtained from human endothelial and primary Tenon's fibroblast cell cultures. Results: The strongest apoptotic effect in both cell groups belonged to paclitaxel, followed by mitomycin C, and despite the overall suppressive effect of the α-tocopherol combination, mitomycin C increased its efficiency on the endothelial cells. The apoptosis/necrosis ratio was highest in α-tocopherol and lowest in paclitaxel, with α-tocopherol generally decreasing necrosis. Bax was observed at a high level with mitomycin C. Cytotoxicity was the highest with paclitaxel, and the caspase-3 reaction was markedly higher with mitomycin C in both cell types. In the α-tocopherol and 5-FU slides, mitosis and a layered formation were observed. The addition of α-tocopherol reduced the cytotoxicity of all antifibrotic agents in both cell series by decreasing the cell numbers, leading to necrosis. Conclusions: Alone or in combination, the use of α-tocopherol and 5-FU is safer than other agents. By suppressing the cytotoxic effects of other antifibrotic agents, α-tocopherol is a promising drug for improving the effects of antifibrotics in many aspects of medicine. In addition, it has the potential to play a role beyond its antioxidant and antifibrotic activity in ocular surgery.